2016
DOI: 10.2993/0278-0771-36.4.881
|View full text |Cite
|
Sign up to set email alerts
|

Stories, Shrines, and Symbols: Recognizing Psycho-Social-Spiritual Benefits of Urban Parks and Natural Areas

Abstract: Executive SummaryWho volunteers to steward the urban forest in New York City and how do volunteer stewards get involved in these activities? This is the second paper in a series that focuses on the social and organizational dynamics of urban environmental stewardship. This paper presents results from research on volunteer stewards at MillionTreesNYC tree planting events in spring and fall 2010, which were sponsored by the New York City Department of Parks and Recreation and the New York Restoration Project, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…Indeed, consistent with previous research [20,32,33], the current study found that using green urban space is, in part, motivated by humans’ deep desire to connect with their loved ones, but also with a larger community around them, with nature, and with their inner selves. This finding is aligned with decades of psychological research that has identified connection as one of the most fundamental human needs that allows people to flourish and feel seen, heard, and valued for who they are [21,48,49,50,51].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, consistent with previous research [20,32,33], the current study found that using green urban space is, in part, motivated by humans’ deep desire to connect with their loved ones, but also with a larger community around them, with nature, and with their inner selves. This finding is aligned with decades of psychological research that has identified connection as one of the most fundamental human needs that allows people to flourish and feel seen, heard, and valued for who they are [21,48,49,50,51].…”
Section: Discussionsupporting
confidence: 90%
“…Previous research [1,20,32,33], the current study, and the lessons from our experimentation of human-centered design suggest that parks are the places where people from all walks of life express themselves, look for connection, and search for what they need and value. As such, parks are like canvases, allowing people to paint different images that symbolize various meanings and convey personal stories.…”
Section: Resultsmentioning
confidence: 66%
“…Globally, urban parks are increasingly used as populations in cities grow. City residents rely on parks and green spaces for physical, mental, and social well-being [1][2][3]. Often, parks are the only or main source of green space for urban dwellers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the results revealed the awareness of participants regarding various relationships, and also confirmed that the relationship formation through 1) connectedness with self, 2) connectedness with neighbors, and 3) connectedness with nature, had effects on reduction in psychological and physical risk factors associated with dementia by alleviating feelings of isolation and enhancing a sense of well being, thus helping them acquire healthy lifestyle habits. This is supported by the results of advanced researches that showed the use of urban green spaces is associated with not only the basic desire for human connection with other people in terms of personal encounters, recreation, and activities, but also with a desire for connection with the larger community, nature and one's inner self (Svendsen et al, 2016).…”
Section: Improvement Of Health-related Lifestylementioning
confidence: 71%